1999
DOI: 10.1093/jn/129.1.113
|View full text |Cite|
|
Sign up to set email alerts
|

Short-Chain Fructo-Oligosaccharide Administration Dose-Dependently Increases Fecal Bifidobacteria in Healthy Humans

Abstract: Short-chain fructo-oligosaccharides (SC-FOS) are a mixture of oligosaccharides consisting of glucose linked to fructose units (Gfn; n = Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
182
2
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(199 citation statements)
references
References 21 publications
12
182
2
3
Order By: Relevance
“…In the two oligofructose fermentations, bifidobacteria increased, which has been observed in many other studies, both in vitro and in vivo (5,12). The bacteriological changes detected by FISH analysis were consistent with the percent-GϩC profiling analysis.…”
Section: Discussionsupporting
confidence: 87%
“…In the two oligofructose fermentations, bifidobacteria increased, which has been observed in many other studies, both in vitro and in vivo (5,12). The bacteriological changes detected by FISH analysis were consistent with the percent-GϩC profiling analysis.…”
Section: Discussionsupporting
confidence: 87%
“…Mushrooms are known to contain many prebiotics such as fructooligosaccharides, b-glucan, and inulin (31). These prebiotics act as sources of nutrition themselves in the large intestine, increasing the number of beneficial bacteria including Bifidobacterium and Lactobacillus (32)(33)(34). In addition, Chang et al reported that dietary supplementation with an extract from the Ganoderma lucidum mushroom increased the relative abundance of Clostridium cluster IV, XIVa, and XVIII in the gut microbiota of mice fed a high fat diet (35).…”
Section: Discussionmentioning
confidence: 99%
“…The prebiotic properties of such supplements have been confirmed in a series of animal and human studies, and have been Proceedings of the Nutrition Society extensively reviewed elsewhere (10) . Subsequent research has shown a dose-dependent effect on luminal bifidobacteria of dietary supplementation with oligofructose (19) and GOS (20) . However, interestingly, the effect of prebiotics naturally occurring in foods has received little attention in the literature, and as yet the inulin and oligofructose content of habitual diet has not been shown to correlate with bifidobacteria in healthy people (21) .…”
Section: Prebiotic Carbohydratesmentioning
confidence: 99%